WAVELET ANALYSIS OF RELATIVE GEOMAGNETIC PALEOINTENSITY AT ODP SITE 983 - Guyodo Y.; Gaillot P.; Channell J.E.T. (My University, 2000)
We performed spectral analysis of the record of relative geomagnetic paleointensity obtained at ODP Site 983, covering the time interval 0-1.1 Ma. The results confirm the presence of significant power at frequencies corresponding to the earth orbital parameters (eccentricity, obliquity, precession). The construction of the evolutionary spectrum allowed us to establish the non-stationarity of the signal at those frequencies. The subsequent use of wavelet techniques made it possible to demarcate the time intervals over which orbital frequencies are present in the record. For those intervals, the paleointensity record shows some coherency with the isothermal remanent magnetization, normalizer of the natural remanent magnetization, and the ratio anhysteretic remanent magnetization/k. These results suggest that the orbital frequencies embedded in the paleointensity record are the expression of lithologic variations, and probably not a characteristic of the geodynamo itself. Extracting (filtering) these wavelet components from the Site 983 paleointensity record indicates, however, that this secondary overprint is of sufficiently low level that it has a minor effect on the overall character of the record.
Keywords: PALEOMAGNETISM; WAVELETS; ANALYSIS; MAGNETIC INTENSITY; SPECTRAL ANALYSIS